2005
DOI: 10.1038/sj.ijo.0803067
|View full text |Cite
|
Sign up to set email alerts
|

Lower mean weight after 14 days intravenous administration peptide YY3–36 (PYY3–36) in rabbits

Abstract: Objective: Endogenous peptide YY ) is associated with postprandial regulation of appetite. We investigated the safety and effectiveness of peripherally administered synthetic human PYY 3-36 for 14 days in New Zealand white rabbits. Weight gain and food consumption were assessed and pharmacokinetics and toxicity characterized. Research methods and procedures: In all, 24 animals were randomized to one of four intravenous treatment groups -control (0.9% saline) or PYY 3-36 bolus at 4.1, 41.0, or 205 mg/kg/day.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 15 publications
3
13
0
Order By: Relevance
“…Peripheral administration of PYY in rodents decreased appetite and food intake [66][67][68], and also reduced body weights in other experimental animals [69,70]. In human, intravenous infusion of PYY 3-36 also showed the same results, indicating the role of PYY as an anorexigenic peptide [71].…”
Section: Peptide Tyrosine Tyrosinesupporting
confidence: 64%
“…Peripheral administration of PYY in rodents decreased appetite and food intake [66][67][68], and also reduced body weights in other experimental animals [69,70]. In human, intravenous infusion of PYY 3-36 also showed the same results, indicating the role of PYY as an anorexigenic peptide [71].…”
Section: Peptide Tyrosine Tyrosinesupporting
confidence: 64%
“…PYY(3-36) reduces acute food intake in lean, DIO, ob/ob, and db/db mice, and in rats, rabbits, and monkeys, and daily administration of PYY(3-36) causes body weight loss in DIO and ob/ob mice, rats, and rabbits (Batterham et al, 2002;Challis et al, 2003;Cox and Randich, 2004;Halatchev et al, 2004;Pittner et al, 2004;Abbott et al, 2005;Chelikani et al, 2005;Koegler et al, 2005;Moran et al, 2005;Neary et al, 2005;Adams et al, 2006;Sileno et al, 2006;Vrang et al, 2006). PYY(3-36) does not reduce food intake in NPY2 knockout mice, or when it is coadministered with the NPY2 antagonist BIIE0246 in wild-type rats, suggesting that the anorexigenic effect of PYY(3-36) is mediated specifically through the NPY2 receptor (Batterham et al, 2002;Abbott et al, 2005).…”
Section: 24-triazolidin-4-yl)ethyl]amino]carbonyl]butyl]-1-[2-mentioning
confidence: 99%
“…Although there was initially some contention regarding the effects of PYY 3À36 on energy intake in animal models, 24 a number of research groups have demonstrated that peripheral PYY 3À36 inhibits food intake and reduces body weight gain in several species. [25][26][27][28][29][30] In the first study of the effects of PYY 3À36 on food intake in humans, spontaneous food intake was reduced by 30% at plasma levels similar to those seen physiologically. 25 A further recent study observed a dosedependent reduction in appetite and food intake in response to intravenous PYY 3À36 administration in normal weight volunteers, although nausea occurred at higher doses.…”
Section: Inhibitors Of Dipeptidyl Peptidase IVmentioning
confidence: 91%